The E3 Ubiquitin Ligase TRIM25 Inhibits Tembusu Virus Replication in vitro - Kaikai, Han; Zhao, Dongmin; Liu, Yuzhuo; Liu, Qingtao; Huang, Xinmei; Yang, Jing; Zhang, Lijiao; Li, Yin (Frontiers in Veterinary Science, 2021)
Duck Tembusu virus (DTMUV) is a newly emerging pathogenic flavivirus that has caused significant economic losses to the duck industry in China since 2010 due to egg production losses and neurological dysfunction. DTMUV is a public health concern because the infection spreads rapidly among birds. Retinoic acid-inducible gene-I (RIG-I) serves as an innate immune sensor and plays a key role in host antiviral defenses. Tripartite motif-containing protein 25 (TRIM25), an E3 ubiquitin ligase, is pivotal for RIG-I ubiquitination and activation. In addition, TRIM25 acts as an interferon-stimulated gene and mediates the antiviral activity. However, the effect of duck TRIM25 on DTMUV has not been assessed. Herein, we report the antiviral function of TRIM25 against DTMUV. First, we constructed the pcDNA3.1-c-myc-duTRIM25 plasmid. TRIM25 has a 2052 bp open reading frame that encodes a predicted 684 amino acid protein consisting of a RING finger domain, a B-box domain, a coiled-coil domain, and a PRY/SPRY domain. The protein sequence identity with chicken, mouse, and human TRIM25 is 69.7%, 47.8%, and 48.3%, respectively. TRIM25 was up regulated in BHK-21 cells, duck embryo fibroblasts, and 293T cells upon DTMUV infection. The expression of viral RNA and proteins was significantly lower in cells over expressing TRIM25 than in control cells. Furthermore, siRNA-mediated silencing of TRIM25 increased the production of viral progeny. These results help elucidate the molecular mechanisms underlying the host response to DTMUV infection and suggest potential control measures for DTMUV outbreaks.